Steel corrosion inhibition ability comparison of piperidin-1-ylmethanephosphonic acid and piperidin-1-ylmethanesulfonic acid: A study of quantum chemical calculation - Hương, Đinh Quý (Hue University Journal of Science: Natural Science, 2023)
Quantum chemical parameters related to the corrosion inhibition activity of PPA (Piperidin-1-ylmethanephosphonic acid) and PSA (Piperidin-1-ylmethanesulfonic acid) compounds, such as the highest occupied molecular obitan energy (EHOMO), the lowest unoccupied molecular orbital energy (ELUMO), the energy gap (ΔEL-H), chemical hardness (η), softness (S), and the transferred electrons number between the inhibitor molecule and iron surface (ΔN), have been calculated at the theoretical level B3LYP/6-311++ G(d,p). The results show that PPA can inhibit iron corrosion better than PSA. In addition, molecular dynamics simulation has shown the adsorption configuration of the protonated inhibitor molecules on the Fe(110) surface. The binding energies of pPPA-N and pPSA-N on Fe(110) surface have values of -570.43 and 558.17 kJ/mol, respectively. This confirms the good Fe surface protection ability of PPA compared with PSA in an acidic medium.